Use of the normalized word vector approach in document classification for an LKMC - Parker, K.; Williams, Robert; Nitse, P.; Tay, A. (Informing Science Institute, 2008)
In order to realize the objective of expanding library services to provide knowledge managementsupport for small businesses, a series of requirements must be met. This particular phase of a largerresearch project focuses on one of the requirements: the need for a document classificationsystem to rapidly determine the content of digital documents. Document classification techniquesare examined to assess the available alternatives for realization of Library Knowledge ManagementCenters (LKMCs). After evaluating prominent techniques the authors opted to investigate aless well-known method, the Normalized Word Vector (NWV) approach, which has been usedsuccessfully in classifying highly unstructured documents, i.e., student essays. The authors proposeutilizing the NWV approach for LKMC automatic document classification with the goal ofdeveloping a system whereby unfamiliar documents can be quickly classified into existing topiccategories. This conceptual paper will outline an approach to test NWV's suitability in this area.